Career-focused teaching and its effects on students’ biology-technical-vocational-fused skills - R. Honra, Joelash; C. Monterola, Sheryl Lyn; T. Yangco, Rosanelia (Institute of Advanced Engineering and Science, 2024)
The K to 12 program in the Philippines, initiated in 2012, brought about challenges like job mismatch among senior high school (SHS) graduates. Addressing this issue requires integrating technical-vocational-livelihood (TVL) skills with core subject skills, particularly in biology. This study explores how the career-focused teaching approach (CFTA) nurtures biology-technical-vocational-fused skills (BTVFS). Using a pretest-posttest quasi-experimental design, two grade 11 classes (35 students each) participated-one exposed to CFTA and the other to conventional teaching. Quantitative data from a researcher-made BTVFS questionnaire were analyzed with an independent samples t-test, revealing significant differences in all BTVFS subcomponents; t(68)=3.670, p<0.036. Qualitative data from reflective journals aligned with BTVFS subskills (metacognition, communication, problem-solving, and collaboration). CFTA proved instrumental in enhancing the BTVFS of students, emphasizing its importance in the curriculum across SHS core subjects to mitigate job mismatch for K to 12 graduates.